P. 1
Laplace Table

Laplace Table

|Views: 5|Likes:
Published by Thanon Daengmanee

More info:

Published by: Thanon Daengmanee on Jul 15, 2011
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

11/15/2013

pdf

text

original

S.

Boyd

EE102

Table of Laplace Transforms
Remember that we consider all functions (signals) as defined only on t ≥ 0.

General

f (t) f +g αf (α ∈ R) df dt dk f dtk
t

F (s) = F +G αF

0

f (t)e−st dt

sF (s) − f (0) sk F (s) − sk−1 f (0) − sk−2 f (τ ) dτ G(s) = F (s) s df dk−1 f (0) − · · · − k−1 (0) dt dt

g(t) =

0

f (αt), α > 0 eat f (t) tf (t) t f (t) f (t) t g(t) = 0 0≤t<T ,T ≥0 f (t − T ) t ≥ T
k

1 F (s/α) α F (s − a) − dF ds
kd k

(−1)
∞ s

F (s) dsk

F (s) ds

G(s) = e−sT F (s)

1

k≥0 k! eat cos ωt sin ωt cos(ωt + φ) e−at cos ωt e−at sin ωt 1 s 1 sk 1 s2 1 sk+1 1 s−a s2 s2 1/2 1/2 s = + 2 +ω s − jω s + jω 1/2j ω 1/2j − = 2 +ω s − jω s + jω s cos φ − ω sin φ s2 + ω 2 s+a (s + a)2 + ω 2 ω (s + a)2 + ω 2 2 .Specific 1 δ δ (k) t tk .

and apply the formula consistently. g has a jump at t = 0. In contrast to f above. In the first case. As a result. g(t) = 1 for t > 0.e. whereas g does. Now let’s apply the derivative formula above. f is the constant function with value 1. so the formula reads L(g ) = 1 = sG(s) − 0 which again is correct. In other words.. Now let’s apply the derivative formula above. 3 . f has no impulsive term at t = 0.Notes on the derivative formula at t = 0 The formula L(f ) = sF (s) − f (0− ) must be interpreted very carefully when f has a discontinuity at t = 0. g = δ. so they have the same Laplace transform. and g(0− ) = 0. and has no discontinuity at t = 0. while in the second case g does. let’s suppose that g is a unit step function. so the formula reads L(f ) = 0 = sF (s) − 1 which is correct. i. We have G(s) = 1/s (exactly the same as F !). In these two examples the functions f and g are the same except at t = 0. f has no jump at t = 0. In this case. As long as you keep track of whether your function has. We’ll give two examples of the correct interpretation. or doesn’t have. suppose that f is the constant 1. Then we have f = 0. a jump at t = 0. First. and g(0) = 0. and f (0− ) = 1 (since there is no jump in f at t = 0). everything will work out. Now. We have F (s) = 1/s.

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->